Association between serum vitamin D level and tuberculosis in children - Ahmad Zaeni Syafii; Abdurachman Sukadi; Budi Setiabudiawan (Indonesian Pediatric Society, 2008)
Background A possible association between vitamin 0 andtuberculosis has been described. In adult, vitamin 0 is consideredto have a role in protecting tuberculosis. On the other hand,tuberculosis infection can decrease serum vitamin 0 level.Objective To find out the difference between serum vitamin 0level in children with and without tuberculosis, and to find theassociation of serum vitamin 0 level with tuberculosis.Methods A cross sectional study was conducted in Cibabat Hospital,Ban dung from July to October 2007. We selected children :S 14years, diagnosed as tuberculosis, and had positive response aftertwo month treatment; for control we selected randomly siblingsor neighbors who didn't have tuberculosis. We excluded childrenwith liver abnormalities and immunocompromized children.Mann-Whitney test and OR method with 95% confidence intervalwas used to analyze the data.Results Thirty-nine children with tuberculosis (21 boys, 18 girls)and 39 children without tuberculosis (19 boys, 20 girls) as wereenrolled. Mean serum vitamin 0 level of children with and withoutTB were 4 7 (SO 25) pmol/L and 125 (SO 3 7) pmol/L, respectively(P=O.OOl). All children without tuberculosis had normal vitamin0 level while of those with tuberculosis, 14 children had normallevel and 25 children were deficient (corrected OR: 139, 95%CI8 to 238).Conclusion Serum vitamin 0 level is low in children withtuberculosis.